Problem 1
Answer: y = 2x^2-4x-6
--------------------------------
Step-by-step explanation:
The x intercepts are -1 and 3, meaning that (x+1) and (x-3) are factors.
This is because x = -1 leads to x+1 = 0 when you add 1 to both sides. And x = 3 leads to x-3 = 0 when you subtract 3 from both sides.
The quadratic equation would be y = a(x+1)(x-3) = a(x^2-2x-3) for some constant 'a'. Use the point (x,y) = (1,-8) to find the value of 'a'.
y = a(x^2-2x-3)
-8 = a(1^2-2*1-3)
-8 = a(-4)
-4a = -8
a = -8/(-4)
a = 2
Therefore,
y = a(x^2-2x-3)
y = 2(x^2-2x-3)
y = 2x^2-4x-6
======================================================
Problem 2
Answer: y = -x^2+x
--------------------------------
Step-by-step explanation:
We'll follow the same idea as the previous problem.
The factors are (x-0) and (x-1). This is the same as saying the factors are x and (x-1)
So we have y = ax(x-1) = a(x^2-x)
Plug in (x,y) = (2,-2) and solve for 'a'.
y = a(x^2-x)
-2 = a(2^2-2)
-2 = a(2)
2a = -2
a = -2/2
a = -1
The equation updates to
y = a(x^2-x)
y = -1(x^2-x)
y = -x^2+x